ACHIEVEMENTS OF THE HIGH AUTHORITY FOR TRANSPARENCY, PREVENTION AND COMBATING CORRUPTION THROUGH THE 2022 ANNUAL REPORT - Kezadri Zhira, (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to shed light on the High Authority for Transparency, Prevention and Combating Corruption as an independent constitutional institution established to promote the principles of transparency, integrity and accountability in the management of public funds, and to reduce the phenomenon of corruption, which is one of the pillars upon which the rule of law is built. The establishment of this institution came in response by the constitutional founder to the international and regional conventions ratified by Algeria, which urge in their content the necessity of reducing the phenomenon of corruption. This was reinforced by the constitutional amendment of 2020, which included many provisions that enshrine the principles of transparency, integrity and accountability in the management of public funds and property. The High Authority for Transparency, Prevention and Combating Corruption was established pursuant to Articles (204-205), granting it broader powers than those previously granted to the National Authority for the Prevention of Corruption. Within the framework of the powers granted to the High Authority, the annual report for the year 2022 was issued, which included many of the Authority’s achievements in combating corruption, which warrant citing it.